Education on Legality, Quality Assurance and Sustainability of 'Jamu Jogorogo' Production in Empowering Women Farming Groups - Wicaksono, Arko Jatmiko; Wahyuningsih, Mae Sri Hartati; Syarif, Rul Afiyah; Padmawati, Retna Siwi; Lestari, Beni; Ranti, Imaniar (Universitas Padjadjaran, 2024)
Production of ‘Jamu Jogorogo’ herbal medicine product by the Group of Women Farmers (KWT Singosaren), in Kab. Bantul, Yogyakarta is stagnant after receiving a Dana Keistimewaan Provinsi (Yogyakarta Province’s Special Fund), and has passed a halal certificate. Based on the Ishikawa fishbone analysis, basic knowledge of legal aspects, quality, and marketing strategy. This study was designed to evaluate the effectiveness of an educational strategy applied to the members of KWT Singosaren. This strategy was implemented through a ‘one-day training’ that began with a Pretest, Post-test I, and Post-test II. A total of 80 members of KWT Singosaren were involved in this training, and 59 met the eligible criteria. A Pretest was conducted before the training to get the initial. After the training, participants worked on the Post-test I. Before leaving the training location, all participants were given a pocketbook containing training material for self-learning. Two weeks (14 days) later, they were asked to take the Post-test II, so the participant’s final knowledge could be investigated. As a result, it was found that there is a rising knowledge of 113.56 % and 71.96 % regarding the understanding of ‘quality’ and ‘legality’, respectively. Interestingly, the marketing strategy (product appeal) and sustainable production knowledge rose by 15.25%. Even so, after Post-test II an increase in scores still occurred. This indicates that participants successfully conducted the self-learning process. Post actualization period, we found that the SPP-IRT permits (legal permits for food production for the Home Industry) of 3 (three) herbal products were successfully issued. Keywords: Empowerment, women, effectiveness, knowledge, training.